Analysis of Three Compounds in Flos Farfarae by Capillary Electrophoresis with Large-Volume Sample Stacking - Hai-xia Yu; Zeng-Yan Hao; Lu Li; Ya-yun Huang; Hong-Fen Zhang; An-jia Chen (International Journal of Analytical Chemistry)
The aim of this study was to develop a method combining an online concentration and high-efficiency capillary electrophoresis separation to analyze and detect three compounds (rutin, hyperoside, and chlorogenic acid) in Flos Farfarae. In order to get good resolution and enrichment, several parameters such as the choice of running buffer, pH and concentration of the running buffer, organic modifier, temperature, and separation voltage were all investigated. The optimized conditions were obtained as follows: the buffer of 40 mM NaH2P04-40 mM Borax-30% v/v methanol (pH 9.0); the sample hydrodynamic injection of up to 4 s at 0.5 psi; 20 kV applied voltage. The diode-array detector was used, and the detection wavelength was 364 nm. Based on peak area, higher levels of selective and sensitive improvements in analysis were observed and about 14-, 26-, and 5-fold enrichment of rutin, hyperoside, and chlorogenic acid were achieved, respectively. This method was successfully applied to determine the three compounds in Flos Farfarae. The linear curve of peak response versus concentration was from 20 to 400 µg/ml, 16.5 to 330 µg/mL, and 25 to 500 µg/mL, respectively. The regression coefficients were 0.9998, 0.9999, and 0.9991, respectively.